Antidumping and safeguard mechanisms : the brazilian experience, 1988-2003 - Kume, Honorio (Policy research working paper, 2005)
"The authors focus on the evaluation of the antidumping regime from 1988 through 2003. During these years the Brazilian economy had to cope with several periods of macroeconomic instability and overvaluation of the domestic currency, particularly from 1990-92 and 1994-98. As a result, from 1992 through 1998, import volumes increased significantly. Although during these years, the demand for antidumping protection was growing, the number of investigations concluded with an affirmative determination was only 52 percent. The authors explain that the institutional framework in charge of administering the antidumping regime was subject to several reforms. Along this process, the Ministry of Development, Industry, and Trade saw its role strengthened. This ministry has a more protectionist bias than the Ministry of Finance that, during the initial years of the liberalization program, played a prominent role in decisions regarding antidumping investigations and measures. The authors conclude that in comparison with other countries that are important users of the antidumping mechanism, the Brazilian experience reveals two interesting features: 1) A relatively small rate of final positive determinations. 2) A tradition of applying antidumping duties in amounts that on average have been quite lower than the full dumping margins. "--World Bank web site